Authority and Power in Social Interaction 2019
DOI: 10.4324/9781351051668-5
|View full text |Cite
|
Sign up to set email alerts
|

Bodies, Faces, Physical Spaces and the Materializations of Authority

Abstract: This chapter presents three perspectives that show what kind of difference bodies, spaces, and other physical aspects make in interaction and how that difference can be analyzed in terms of power and authority. The first perspective, presented by Vincent Denault and Pierrich Plusquellec, consists in considering the human body not only as a subject but also as the object of analysis and reflects on ways in which experimental research on nonverbal communication may complete observation of naturally occurring int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Acknowledging that decidability need not be fixed in a person or position, however, indicates that locating or placing authority is always an achievement of communicative practices (Kuhn & Jackson, 2008). CCO thinking proceeds a step further, arguing that it is not merely the faculty member who decides what is taught; instead, it is always a confluence of agencies, most of which are largely 'hidden,' that decides such matters (Bencherki et al, 2020). And, if many such agencies operate, there is the possibility of contestation: a competition for authority in writing the trajectory of practice (Kuhn, 2008).…”
Section: Ccle: Classroom Practice and Authoritymentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledging that decidability need not be fixed in a person or position, however, indicates that locating or placing authority is always an achievement of communicative practices (Kuhn & Jackson, 2008). CCO thinking proceeds a step further, arguing that it is not merely the faculty member who decides what is taught; instead, it is always a confluence of agencies, most of which are largely 'hidden,' that decides such matters (Bencherki et al, 2020). And, if many such agencies operate, there is the possibility of contestation: a competition for authority in writing the trajectory of practice (Kuhn, 2008).…”
Section: Ccle: Classroom Practice and Authoritymentioning
confidence: 99%
“…This means that focusing attention on broader structural mechanisms will reveal little about what actually happens in the classroom, for if we are to understand how content is decided upon and taught we need to assert a communicational rendering of MLE, i.e., CCLE. (Bencherki, et al, 2020) in the management classroom. It may be assumed that it is the teacher/educator (Dean & Forray, 2021;Vasilyeva, Robles, Saludadez, Schwägerl, & Castor, 2020), playing an identifiable formal role, who decides what is to be taught and how learning is to be accomplished.…”
Section: And Furthermentioning
confidence: 99%
“…Our analysis is guided by a ventriloquial approach, which “focuses not only on speaking and doing, but also, and maybe especially, on making one speak or making one do something” and whose figures “often act as a source of authority ” (emphasis in original; Bencherki et al, 2020, p. 89). Theresa Castor and Jean Saludadez (in a section, titled, “The Varieties of (More or Less) Formal Authority,” of a larger chapter by Vasileyva et al, 2020) suggested a three-step process when conducting a ventriloquial analysis: (1) record interactions as they happen or collect recorded interactions; (2) identify markers through which a variety of figures recurrently and iteratively express themselves in interaction; and (3) interpret or make inferences about what the figures are made to say or do (Vasilyeva et al, 2020).…”
Section: Ventriloquial Analysis As a Mode Of Inquirymentioning
confidence: 99%
“…The analysis involved a close reading of field notes, pamphlets, and webpages, with the goal of identifying all figures invoked to speak on behalf of the organization of Faith Pregnancy Center. Following Castor and Saludadez’s (see Bencherki et al, 2020) ventriloquial analysis process, we identified several interactions that surfaced across the data and the markers, or figures, that continually shaped, upheld, and mobilized Faith Pregnancy Center’s organizational presence. Through this process, we found that authority figures were marked by medical knowledge and procedure (references to “medical director,” “board certified,” “Commitment to Care,” and research studies reinforcing medical credibility—“The research is clear”); religion (evocation of “God” and biblical passages); educational/philanthropic appeal (references to “free” classes, resources, and community partnership—“Faith will be available to serve and assist you ...”); and what Castor and Saludadez identify as collectives (the use of we —“ We offer ...”, “ We are here ...”).…”
Section: Ventriloquial Analysis As a Mode Of Inquirymentioning
confidence: 99%
See 1 more Smart Citation